The behaviour of square sandwich panel Part I: under static loading - Alias, Amran (Penerbit UTM Press, 2007)
This series of papers on behaviour of square sandwich panel consists of two parts. In part I, the performance and behaviour of the square sandwich panel under static loading was first examined. The sandwich panel was centrally loaded by using hemispherical and flat indenters on their respective support units. The panel materials used specifically for this project are mild steel skin and PVC foam namely R55 and polyurethane (PU) foam cores. The aim of this study is to obtain experimental evidence of the failure modes of square sandwich panels under concentrated load at the centre of panels, simply supported at the four edge corners for the square panel. After static tests, the whole curves for each panel were determined. The relation between the observed damage development, the property of degradation during the static test of the panels was investigated. In part II, the dynamic tests will be conducted in order to determine the performance, behaviour, effect of foam’s type and the correlation between input energy from static and dynamic tests.